Respuestas

2012-12-16T21:05:41+01:00

es cuestion de remplazar los valores de "x" solicitados.

A) 4x^3 - 2x +6, para a x=1----> 4(1)^3-2(1)+6=8

B) 4x^3 - 2x + 6 para x = -1----> 4(-1)^3-2(-1)+6=4

C)2x^2 + 7x + 2 para x = 2-----> 2(2)^2+7(2)+2=24

D)2x^2 + 7x + 2 para x = -2-----> 2(-2)^2+7(-2)+2=-4

ESPERO QUE TE SIRVA, SALUDOS

 
2012-12-16T21:07:11+01:00

A) 4x^3 - 2x +6, para a x=1........... 4(1)^3-2(1)+6=8

B) 4x^3 - 2x + 6 para x = -1............4(-1)^3-2(-1)+6=4

C)2x^2 + 7x + 2 para x = 2.............2(2)^2+7(2)+2=24

D)2x^2 + 7x + 2 para x = -2............2(-2)^2+7(-2)+2=-4